Economic Mobility in Europe and Central Asia : Exploring Patterns and Uncovering Puzzles - Cancho, Cesar; Davalos, Maria E.; Demarchi, Giorgia; Meyer, Moritz; Sanchez Paramo, Carolina (World Bank Group, Washington, DC, 2015)
Substantial upward economic mobility in the majority of countries in Europe and Central Asia in the 2000s translated into achievements in reducing poverty and boosting shared prosperity. Although factors associated with upward mobility vary significantly by country, education and jobs undoubtedly play an important role in lifting households out of poverty and helping them to improve their living standards. This study finds there is a puzzling mismatch between the objective economic mobility patterns observed in survey data and people's subjective perception of their mobility. A majority of people in the region perceives they are worse off economically than in the past and voice frustration over limited opportunities to improve their lives. This disconnect is partly explained by increased inequality in the region, an increasing sense of unfairness in the processes to move up, and a more marked sense of insecurity and vulnerability. Although the region has been making headway in lifting households out of poverty, ensuring sustainable progress toward poverty reduction and shared prosperity requires policies that promote human capital accumulation, foster job creation, and offer adequate protection to improve households' resilience to shocks.